Iconography and wetsite archaeology of Florida's watery realms - Wheeler, Ryan J.; Ostapkowicz, Joanna (Ripley P. Bullen series., 2019)
Frank Hamilton Cushing's 1896 excavations at Key Marco revealed astonishing carved and painted objects of wood rarely seen by archaeologists. The chapters in this book explore new discoveries and revisit existing museum collections, asking new questions or employing innovative analytical techniques. While we might reach a different conclusion today, it's clear that ancient Florida is difficult to comfortably place within the Southeast or Caribbean and that much of that difficulty arises from the iconography born of Florida's watery landscapes.